Methods for the Classification of Radar Objects (Nexo Revista Científica, 2022)
Currently, many different algorithms have been developed that implement the classification problem. Of particular interest is the use of automatic classification algorithms in radar systems. In each such system, one has to solve the classification and recognition problem for detected targets. The work of an operator analyzing the information can take place in conditions that hinder assess of the control object’s state. This is due to the absence or insufficient amount of reliable information about some radar target properties. A radar target is understood as any material object that can be detected, and its location and movement parameters can be measured using radar methods. We consider air, ground and surface objects as a radar object. Object classification algorithms are used in various fields when analyzing the properties of an object. This paper discusses the main methods for the classification of radar objects.